Design and implementation of three-phase self-boosting voltage and current integrated standard device - SHI Haoyuan; XIN Xiaogang; DANG Shaojia; ZHANG Fan; LIU Xiaokai (Diance yu yibiao)
Existing three-phase combined transformer metrological performance verification test exists in the number of required equipments, test wiring complexity, low efficiency and other issues, this paper analyzes the leakage of current and the mutual influence of the various components through the construction of the system electromagnetic perturbation on the integration of the standard characteristics of the impact of the equivalent model, and puts forward the design of the self-boosting high-voltage current standard transformer with shielding and the optimization of the structural layout of the active shielding technology, the development of the highly integrated three-phase self-boosting voltage and self-boosting current standard device for 35 kV and below has realized the integration of three-phase combined transformer standard device, easy wiring, high efficiency of work, which greatly improves the test efficiency and safety, lays a foundation for the optimization of the subsequent three-phase combined transformer calibration device, and provides a powerful technical support for the safe, accurate and efficient full performance testing of power transformers in distribution network.